2022
DOI: 10.3390/cancers14020373
|View full text |Cite
|
Sign up to set email alerts
|

BHMPS Inhibits Breast Cancer Migration and Invasion by Disrupting Rab27a-Mediated EGFR and Fibronectin Secretion

Abstract: Our previous work demonstrated that (E)-N-benzyl-6-(2-(3, 4-dihydroxybenzylidene) hydrazinyl)-N-methylpyridine-3-sulfonamide (BHMPS), a novel synthetic inhibitor of Rab27aSlp(s) interaction, suppresses tumor cell invasion and metastasis. Here, we aimed to further investigate the mechanisms of action and biological significance of BHMPS. BHMPS decreased the expression of epithelial-mesenchymal transition transcription factors through inhibition of focal adhesion kinase and c-Jun N-terminal kinase activation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…Slp4 (also known as granuphilin) interacts with Rabs via its N-terminal Slp homology domain and binds to SNARE complex via a central linker region [108]. Park et al reported that disrupting the interaction between Rab27a and Slp4 with inhibitor BHMPS reduced exosome secretion and inhibited tumor growth of breast cancer cells [109]. Munc13-4 is another effector of Rab27.…”
Section: Rab Gtpasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Slp4 (also known as granuphilin) interacts with Rabs via its N-terminal Slp homology domain and binds to SNARE complex via a central linker region [108]. Park et al reported that disrupting the interaction between Rab27a and Slp4 with inhibitor BHMPS reduced exosome secretion and inhibited tumor growth of breast cancer cells [109]. Munc13-4 is another effector of Rab27.…”
Section: Rab Gtpasesmentioning
confidence: 99%
“…The mechanism of MVB transport and fusion with the plasma membrane can also be exploited by cancer. Rab27a/b are aberrantly expressed in cancers, and they have a key function in cancer progression via their activity in exosome biogenesis [109,153]. In addition, depletion of elements that mediates ER-endosome contact sites or invadopodia formation, such as Rab7, Protrudin, FYCO1, fascin-1, and cortactin, blocks exosome biogenesis and inhibits invasion in NSCLC and breast cancer [104,129,132].…”
Section: Aberrant Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that calpain inhibitors, calpeptin, and Rho-associated protein kinases (ROCK), Y27632, can block MVB formation and release by targeting cytoskeletal proteins . Apart from that, targeting Rab27-related signaling, as well as the syndecan-syntenin-Alix signaling has also shown promising outcomes in inhibiting the EVs biogenesis of cancer. , However, since the ESCRT machinery is exploited by all cells to generate EVs, interfering with ESCRT-related signaling pathways may cause severe side effects by blocking the EV-mediated cell–cell communications required for normal organ functions. As accumulated evidence suggests that highly malignant cancer cells are able to secrete more EVs compared to normal cells, there might be some alternative mechanisms for cancer cells to generate and release EVs into the extracellular space.…”
Section: Recent Progress In Anticancer Therapy Targeting Cancer-assoc...mentioning
confidence: 99%
“…Rab27a and Rab27b interact with their respective effector proteins, Slp4 and Slac2b, respectively, to transfer MVBs from the perinuclear to the periphery area of the cell [25]. Abolishing these interactions leads to decreased exosome release and inhibited breast cancer cell invasion and migration [27]. Additionally, some factors such as HSP90 and lysosome-associated protein transmembrane-4B (LAPTM4B) also transfer MVBs toward the periphery to promote their secretion [28,29].…”
Section: Exosome Secretionmentioning
confidence: 99%